Code of practice for selection, installation and maintenance of electrical apparatus for use in potentially explosive atmospheres (other than mining applications or explosive processing and manufacture). Recommendations for type of protection 'e'. Increased safety Part 6, (31st March 1978) - British Standards Institution
No abstract available